Effects of Different Water and Nitrogen Supply Modes on Peanut Growth and Water and Nitrogen Use Efficiency under Mulched Drip Irrigation in Xinjiang - Jianshu Dong; Zhu Xue; Xiaojun Shen; Ruochen Yi; Junwei Chen; Qiang Li; Xianfei Hou; Haocui Miao (Plants, 2023)
The optimization of irrigation and fertilization indexes for peanuts with drip irrigation is urgently needed in Xinjiang. A field experiment was conducted during the 2021 peanut growing season at Urumqi, Xinjiang, in Northwestern China, to evaluate the effects of different water and nitrogen treatments on the growth, yield, and water and nitrogen utilization of peanuts. In field experiments, we set up three irrigation levels (irrigation water quotas of 22.5, 30, and 37.5 mm, respectively, for W1, W2, and W3), two nitrogen application levels (77.5 and 110 kg·ha−1, recorded as N1 and N2), and a control treatment (W2N0) that did not include the application of nitrogen. The results showed that nitrogen application enhanced the growth, physiological indexes, yield, and water use efficiency of the W1, W2, and W3 treatments when the irrigation volume remained the same. In comparison with no nitrogen application (W2N0), the peanut growth, physiological indexes, yield, and water use efficiency improved with increasing irrigation amounts in the N1 and N2 treatments. With an increase in the irrigation volume, the water use efficiency grew; the W3N2 treatment had the highest water use efficiency, which was 1.32 kg·m−3. The total water consumption and reproductive-stage water consumption of the peanuts in all treatments increased with the irrigation volume, and a high yield was achieved at 402.57 mm, which was 5.2974 Mg·ha−1. In the W1, W2, and W3 treatments, the nitrogen partial factor productivity significantly decreased as the nitrogen application increased, with the nitrogen partial factor productivity in the W3N1 treatment being the highest, at 60.61 kg·kg−1. A comprehensive evaluation based on principal component analysis assigned W3N2 the higher score. These findings suggest that irrigation water quotas of 37.5 mm should be coupled with 110 kg·ha−1 nitrogen applications for peanuts using drip irrigation in mulch film in Xinjiang.